Worrying Labour Market Tendencies in the European Union - Annamaria Artner; Krisztina Sőreg (Romanian Journal of European Affairs)
The authors examine the developments that have characterized the European Union labour market in the past decades, relying mainly on Eurostat data. They focus on the tendencies of employment and unemployment in general, the changing conditions of work, the development of “atypical” forms of employment, the associated fluctuations of the social situation reflected in the different measures of poverty and social exclusion, and the distribution of incomes. The researchers touch upon the question of migration from the viewpoint of the European labour market and provide an overview of the community policies of the EU that have aimed at alleviating the problems of employment since 1970. The authors conclude that the EU labour market has been significantly differentiated during the past few decades and the precarious forms of “atypical employment” have grown in weight. The common policies have not been able to prevent the deteriorating tendencies of employment and they do not seem to be more successful in the near future either.